Octahedral substitution in beryl from weakly fractionated intragranitic pegmatite Predne Solisko, Tatry Mountains (Slovakia): the indicator of genetic conditions - Bacik,P.; Fridrichova,J.; Uher,P.; Rybar,S.; Bizovska,V.; Luptakova,J.; Vrablikova,D.; Pukancik,L.; Vaculovic,T. (Journal of Geosciences, 2019)
Crystal-chemical properties, and octahedral substitution role in particular, of beryl from weakly fractionated intragranitic pegmatite Predne Solisko, Vysoke Tatry Mts. (Slovakia) is described in detail. The studied beryl was found in granitic pegmatite derived from biotite I-type granodiorite. It has a weakly zoned core with variable Fe and Mg contents but constantly high Na. The rim zone shows weak irregular chemical zoning with low Na and Mg, the latter dominating over Fe. The total Al content varies between 1.77 and 1.87 apfu; Al is substituted by Fe (0.03-0.07 apfu) and mostly by Mg (0.02-0.13 apfu). The decrease in octahedral site charge is mostly balanced by Na (0.05-0.30 apfu). However, the Na content in the rim is insufficient for balancing octahedral Fe + Mg, implying that at least a part of Fe is ferric. The c/a ratio is typical of “normal” beryl but its low value suggests dominant octahedral substitution. The 2b channel site is occupied by Na, Ca, REE and Sr. At the larger 2a site, Cs is clearly the most abundant (up to 3919 ppm). Water is present as both type I and type II but with large dominance of doubly coordinating H2O type II suggesting relatively fluid-rich genetic environment. The composition of beryl reflects the source rock of pegmatitic melt; I-type granitoids are generally enriched in Mg compared to S-type ones and consequently, the CNaOMgC□-1OAl-1 substitution may play a more important role in beryl from I-type derived pegmatites such as Predne Solisko. The geological position of the studied intragranitic pegmatite excludes the possibility of contamination from the host rock and the beryl chemistry, therefore, reflects faithfully the pegmatitic melt composition.
Keywords: beryl; crystal chemistry; octahedral substitution; site occupancy; intragranitic pegmatite; High Tatras